Stretchable Organic Thin-Film Transistors Fabricated on Elastomer Substrates Using Polyimide Stiff-Island Structures. (4th November 2014) - Jung, Soon-Won; Choi, Jeong-Seon; Koo, Jae Bon; Park, Chan Woo; Na, Bock Soon; Oh, Ji-Young; Lee, Sang Seok; Chu, Hye Yong
Abstract : We demonstrate stretchable organic thin-film transistors (OTFTs) on a polyimide stiff-island/elastomer substrate. All processes are performed entirely at elastomer-compatible temperatures. We confirm the basic properties of the poly(vinylidene fluoride-trifluoroethylene) [P(VDF-TrFE)] with a poly(methyl methacrylate) (PMMA) blended film on the elastomer substrate and evaluate the characteristics of the fabricated stretchable OTFTs. A field-effect mobility of 3.4 × 10 −3 cm 2 V −1 s −1, an Ion /Ioff ratio greater than 10 3, a subthreshold voltage swing of 12.5 V/decade, and a gate leakage current of 10 −10 A were obtained. The endurable maximum strain was approximately 50% for the OTFTs without degrading the field-effect mobility formed on the elastomers.